Cooperación internacional para el desarrollo: gobierno, economía y sociedad. Evolución de las políticas y escenarios futuros - Paolo Dieci (Revista Internacional de Cooperación y Desarrollo, 2017)
Carlo Tassara’s book is full of insights into the policies that guided development assistance over the last decades. The author analyses the historical evolution of development policies from the World War II era to our times. Further to the adoption of the Millennium Development Goals (MDGs) Agenda (2000), a road map from Monterey (Mexico, 2002) to Addis Ababa (Ethiopia, 2015) leads to the 2030 Agenda, including 17 Sustainable Development Goals (SDGs).